A Model of Shield Jack Thrust to Shield Attitude - 郭正刚 孙伟 岳明 (东华大学学报（英文版）, 2011)
The attitude of the shield tunneling machine （ or ＂shield＂ for short） during tunneling is important to tunnel excavation and construction quality, which results from a combination of jack thrust, ground displacement around the shield, and ground mechanics parameters, etc. A shield attitude model involving elements above was proposed. In this model, ground displacement was taken to calculate the load around the shield. Ground mechanics parameters were involved. Based on the shield load model, the needed jack thrust for shield desired attitude was derived. The proposed method is validated using engineering data, and lays reliable foundation for shield attitude control.